GAMBARAN PELAYANAN ADMINISTRASI RAWAT JALAN PADA PASIEN BPJS DI PUSKESMAS SANTONG TAHUN 2024 - Muhaemin, Dody; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Fathurrahman; Lale Ajeng Khalifatun Wardani; Muhammad Aditya Rachman (Nusadaya Journal of Multidiciplinary Studies, 2024)
The administrative service process at the Santong Community Health Center (Puskesmas) has been carried out in accordance with established Standard Operating Procedures (SOPs). BPJS patients follow a process from obtaining a queue number, registering at the counter with document verification, and then being directed to the designated clinic. The e-Puskesmas system has been used for electronic input and processing of medical records, which helps expedite service delivery. Administrative services are considered quite reliable and systematic, but technical challenges persist, such as e-Puskesmas network disruptions, power outages, and patients not carrying their identity cards or active BPJS cards. This causes delays in service, although staff strive to provide services according to procedures. Administrative and medical records staff demonstrate a friendly, polite, and responsive attitude when dealing with patients, including when administrative challenges arise. They also provide easy-to-understand explanations and demonstrate concern, especially for elderly patients or those experiencing difficulties. Facilities such as computers, printers, smart TVs, an electronic queuing system, and other documentation tools support smooth service delivery. However, a backup system is not yet in place to anticipate disruptions that could disrupt the digitalization of the administration process.